ANALISIS KINERJA LIQUID RING VACUUM PUMP UNTUK PENURUNAN TEKANAN KONDENSER UTAMA PADA SISTEM PEMBANGKIT PANAS BUMI BEBAN DAYA 42 MW PT GEO DIPA ENERGI UNIT DIENG - , GILANG RIADI RAMADHANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Based on from the Ministry of Energy and Mineral Resources of Indonesia (KESDM) established in 2011 shows that there are 50 mining work area (WKP) that are scattered around this country. It shows how much potential electrical energy from geothermal sector is in Indonesia, although until now not all WKP have officially operated yet. If we discuss about the utilization of geothermal energy, it will never exclude the waste of gas produced from the bowels of the earth. Gases such as carbon dioxide, hydrogen sulfide, methane, ammonia and other compounds are elements of noncondensable gas (NCG), which can affect the performance of the geothermal system. From load data verification 42 MW had been modeled in Cycle Tempo 5.0, ejector can be modeled with combination of valve and node. LRVP can be modeled with combination of valve and pump. From the modeled data verification with ejector in Cycle Tempo 5.0, produced nett power 34 MW while after modeling geothermal system with LRVP produced nett ower 37 MW. LRVP produced bigger nett power than ejector.